Synergistic Cascade Strategy Based on Modifying Tumor Microenvironment for Enhanced Breast Cancer Therapy - Huan Zhang; Jinshun Xu; Binyang Gao; Hong Wang; Jianbo Huang; Jie Zhou; Rui Yang; Feng Yan; Yulan Peng (Frontiers Media S.A., 2021)
Background: Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer with very few treatment options. Although tumor-targeted nanomedicines hold great promise for the treatment of TNBC, the tumor microenvironment (TME) continues to be a major cause of failure in nanotherapy and immunotherapy. To overcome this barrier, we designed a new synergistic cascade strategy (SCS) that uses mild hyperthermia and smart drug delivery system (SDDS) to alter TME resistance in order to improve drug delivery and therapeutic efficacy of TNBC.Methods: Mild hyperthermia was produced by microwave (MW) irradiation. SDDS were formulated with thermosensitive polymer-lipid nanoparticles (HA-BNPs@Ptx), composed of polymer PLGA, phospholipid DPPC, hyaluronic acid (HA, a differentiation-44-targeted molecule, also known as CD44), 1-butyl-3-methylimidazolium-L-lactate (BML, a MW sensitizer), and paclitaxel (Ptx, chemotherapy drug). 4T1 breast tumor-bearing mice were treated with two-step MW combined with HA-BNPs@Ptx. Tumors in mice were pretreated with first MW irradiation prior to nanoparticle injection to modify and promote TME and promoting nanoparticle uptake and retention. The second MW irradiation was performed on the tumor 24 h after the injection of HA-BNPs@Ptx to produce a synergistic cascade effect through activating BML, thus, enhancing a hyperthermia effect, and instantly releasing Ptx at the tumor site.Results: Multifunctional CD44-targeted nanoparticles HA-BNPs@Ptx were successfully prepared and validated in vitro. After the first MW irradiation of tumors in mice, the intratumoral perfusion increased by two times, and the nanoparticle uptake was augmented by seven times. With the second MW irradiation, remarkable antitumor effects were obtained with the inhibition rate up to 88%. In addition, immunohistochemical analysis showed that SCS therapy could not only promote tumor cell apoptosis but also significantly reduce lung metastasis.Conclusion: The SCS using mild hyperthermia combined with SDDS can significantly improve the efficacy of TNBC treatment in mice by modifying TME and hyperthermia-mediated EPR effects.